Comparison of Heart Rate Variability among Young Malay Male Adult with Different BMI and Level of Adiposity - Juliana, Norsham; Nadia, Mohd Effendy; Roslan, Nadia Ahmad; Ghazali, Ahmad Rohi; Fauzi, Nor Farah Mohamad; Sahar, Mohd Azmani; Sulaiman, Ainul Huda; Hayati, Abd Rahman; Mohamed, Abdul Latiff (IIUM Medical Journal Malaysia, 2019)
INTRODUCTION: Subclinical changes that occur in the heart at an early age may provide valuable information to outline prevention strategies for cardiovascular diseases. Heart rate variability (HRV) reflects regulation of autonomic balance, heart, and vascular tone, which are the determinants of blood pressure. Therefore, this study aimed to determine the difference in heart rate variability (HRV) of Malay male young adult with their BMI and adiposity level. MATERIALS AND METHODS: A total of 201 Malay male young adult aged between 19 to 24 years old were screened and their BMI and adiposity level were measured. Three non -invasive tests; Valsalva Manoeuvre, orthostatic response and 30/15 ratio of heart rate were performed. Short term HRV time and frequency domains were recorded. RESULTS: Despite few significant differences in HRV parameters of overweight/obese subjects, the result is inconclusive to conclude any reduced variability. However, those with high adiposity regardless of their BMI reported significantly lower mean of R -R SD in time domain and lower mean of LF/HF ratio in frequency domain. The orthostatic reflex results revealed that high adiposity subjects had significantly lower mean of LF and HF. A decrement of -0.28 ms2 HF/LF during Valsalva manoeuvre, -0.35 LF ms2 in orthostatic reflex and 0.33 ms2 in orthostatic reflex per 1% of body fat percentage were observed. CONCLUSION: HRV parameters were inversely proportional to the adiposity level which was suggestive of modulation of sympathetic function can occur at an early age.